Type-2 Fuzzy Logic and Systems Dedicated to Professor Jerry Mendel for his Pioneering Contribution - John, Robert; Hagras, Hani.; Castillo, Oscar; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2018)
This book explores recent perspectives on type-2 fuzzy sets. Written as a tribute to Professor Jerry Mendel for his pioneering works on type-2 fuzzy sets and systems, it covers a wide range of topics, including applications to the Go game, machine learning and pattern recognition, as well as type-2 fuzzy control and intelligent systems. The book is intended as a reference guide for the type-2 fuzzy logic community, yet it aims also at other communities dealing with similar methods and applications. .
From T2 FS-based MoGoTW System to DyNaDF for Human and Machine Co-Learning on Go -- Ordered Novel Weighted Averages -- On The Comparison of Model-Based and Model-Free Controllers in Guidance, Navigation and Control of Agricultural Vehicles -- Important and Challenging Issues for Interval Type-2 Fuzzy Control Research -- Type-2 Fuzzy Logic in pattern recognition applications -- Type-2 Fuzzy Logic Control in Computer Games -- A Type-2 Fuzzy Model to Prioritize Suppliers Based on Trust Criteria in Intelligent Agent-Based Systems.
Keywords: Computational intelligence; Artificial intelligence; Control engineering; Pattern recognition systems; Computational Intelligence; Artificial Intelligence; Control and Systems Theory; Automated Pattern Recognition